Perspective-Taking in Sentence Comprehension: Time and Empathy - Tokimoto, Shingo; Tokimoto, Naoko (Frontiers in Psychology, 2018)
This study examines the neural substrate of perspective-taking by analyzing the electroencephalogram (EEG) elicited by the auditory comprehension of sentences for which the comprehender had to adopt the perspective of the person described in them. Recent studies suggest that the ability of perspective-taking can be an integrative function of temporal and spatial information processing. We thus examined the independence and possible interaction of human perspective shifts and temporal perspective-taking by utilizing Japanese subsidiary giving verbs, namely "-ageru" and "-kureru." We manipulated human perspective shifts and temporal perspective-taking independently in experimental sentences by syntactically changing the subject and the object between the speaker and a third person, while we manipulated the tense to be past or non-past tense via sentence-final particles "ru/ta" (non-past/past). The EEG analyses via electrodes indicated the suppression of the beta band for human perspective shifts in sentences in non-past tense and the absence of such suppression in sentences in past tense. The analyses for the clusters of independent components indicated beta suppression for past tense against non-past tense in sentences without a human perspective shift. This response pattern suggested a close relationship between human perspective shift and temporal perspective-taking. The beta suppression for the human perspective shift in our experiment can be understood as a replication of the previous EEG findings observed for perspective-taking in the presentation of visual images. The preceding findings and our result suggest that the ability or the function of perspective-taking is modality-general. Furthermore, the generator of the beta suppression for past tense against non-past tense without human perspective shift was localized in the precuneus, which is consistent with the recent findings indicating that the precuneus is deeply involved in time perception.